Analytical assessment of e-cigarettes : from contents to chemical and particle exposure profiles /: from contents to chemical and particle exposure profiles. (2016) - Farsalinos, Konstantinos E; Gillman, I. Gene; Polosa, Riccardo; Thornburg, Jonathan; Hecht, Stephen S
No abstract available